Ethnic differences in the association of QRS duration with ejection fraction and outcome in heart failure. Issue 18 (11th July 2016) - Gijsberts, Crystel M; Benson, Lina; Dahlström, Ulf; Sim, David; Yeo, Daniel P S; Ong, Hean Yee; Jaufeerally, Fazlur; Leong, Gerard K T; Ling, Lieng H; Richards, A Mark; de Kleijn, Dominique P V; Lund, Lars H; et al.
Abstract : Background: QRS duration (QRSd) criteria for device therapy in heart failure (HF) were derived from predominantly white populations and ethnic differences are poorly understood. Methods: We compared the association of QRSd with ejection fraction (EF) and outcomes between 839 Singaporean Asian and 11 221 Swedish white patients with HF having preserved EF (HFPEF)and HF having reduced EF (HFREF) were followed in prospective population-based HF studies. Results: Compared with whites, Asian patients with HF were younger (62 vs 74 years, p<0.001), had smaller body size (height 163 vs 171 cm, weight 70 vs 80 kg, both p<0.001) and had more severely impaired EF (EF was <30% in 47% of Asians vs 28% of whites). Overall, unadjusted QRSd was shorter in Asians than whites (101 vs 104 ms, p<0.001). Lower EF was associated with longer QRSd (p<0.001), with a steeper association among Asians than whites (pinteraction <0.001), independent of age, sex and clinical covariates (including body size). Excluding patients with left bundle branch block (LBBB) and adjusting for clinical covariates, QRSd was similar in Asians and whites with HFPEF, but longer in Asians compared with whites with HFREF (p=0.001). Longer QRSd was associated with increased risk of HF hospitalisation or death (absolute 2-year event rate for ≤120 ms was 40% and for >120 ms it was 52%; HR for 10 ms increase of QRSd was 1.04 (1.03 to 1.06), p<0.001), with no interaction by ethnicity. Conclusion: We found ethnic differences in the association between EF and QRSd among patients with HF. QRS prolongation was similarly associated with increased risk, but the implications for ethnicity-specific QRSd cut-offs in clinical decision-making require further study.